Costs and Benefits of Transgenerational Induced Resistance in Arabidopsis - López Sánchez, Ana; Pascual-Pardo, David; Furci, Leonardo; Roberts, Michael R.; Ton, Jurriaan (Frontiers in Plant Science, 2021)
Recent evidence suggests that stressed plants employ epigenetic mechanisms to transmit acquired resistance traits to their progeny. However, the evolutionary and ecological significance of transgenerational induced resistance (t-IR) is poorly understood, because knowledge of how parents interpret environmental cues to control such epigenetic responses and the interplay with the anticipated ecological costs is lacking. Here, we have used a full factorial design to study the specificity, costs and transgenerational stability of t-IR following exposure of Arabidopsis thaliana to increasing stress intensities by a biotrophic pathogen, a necrotrophic pathogen, and salinity. We show that t-IR in response to infection by biotrophic or necrotrophic pathogens is effective against pathogens of the same lifestyle. This pathogen-mediated t-IR is associated with ecological costs, since progeny from biotroph-infected parents were more susceptible to both necrotrophic pathogens and salt stress, whereas progeny from necrotroph-infected parents were more susceptible to biotrophic pathogens. Hence, pathogen-mediated t-IR provides benefits when parents and progeny are in matched environments but is associated with costs that become apparent in mismatched environments. By contrast, soil salinity failed to mediate t-IR against salt stress in matched environments but caused non-specific t-IR against both biotrophic and necrotrophic pathogens in mismatched environments. However, the ecological relevance of this non-specific t-IR response remains questionable as its induction was offset by major reproductive costs arising from dramatically reduced seed production and viability. Finally, we show that the costs and transgenerational stability of pathogen-mediated t-IR are proportional to disease pressure experienced by the parents, suggesting that plants use disease severity as an environmental proxy to adjust investment in t-IR.